An overview of electrical energy consumption trends in Malaysian Government Hospitals : a case study of Serdang Hospital - Azrin Bin Mohd Din (Kulliyyah of Architecture and Environmental Design,International Islamic University Malaysia, 2012)
Hospitals have unique and intensive energy use requirements. In addition to the need for lighting and heating 24 hours a day, hospitals demand extensive energy for ventilation, equipment, sterilization, and laundry and food preparation. Studies on ho.spitals abroad have shown that lighting contributes about 25 percent and HV AC contributing almost 45 percent of a typical hospital's energy bill. Those studies also show that energy saving initiatives have the potential to reduce energy cost significantly. This study aims to compare the Building Energy Index (BEi) and load apportioning performance of different public hospitals in Malaysia with specific focused example of Serdang Hospital which no audit has been done yet. Serdang Hospital was selected for this study since it is one of the recently commissioned and operationalised hospital in the Klang Valley. The data was collected over 24 hour electricity utilisation for a one week period by using datalogger tool to map the energy consumption trend. The detailed audit study was summarised and compared with other BEi's compiled from secondary sources. A comparison is made between the energy use trends of different hospitals. Discussion is done on the possible approach towards increased energy savings in hospitals.